Accuracy and Precision of Actigraphy and SMARTwheels for Measuring Push Counts Across a Series of Wheelchair Propulsion Trials in Non-disabled Young Adults - Soleymani, Hunter; Jeng, Brenda; Abdelmessih, Beshoy; Cowan, Rachel; Motl, Robert W. (International Journal of Medical Students, 2023)
Background: There has been a growing interest in “Lifestyle Physical Activity” (LPA) among wheelchair users. LPA can be quantified via “pushes” as an outcome metric. This study examined the accuracy and precision of research-grade devices for counting pushes across a series of wheelchair propulsion trials. Methods: Eleven non-disabled, young adults completed 19, 1-minute wheelchair propulsion trials at self-selected speeds with a wheelchair equipped with a SMARTwheel (SW) device while being video recorded. Participants also wore 2 ActiGraph accelerometers, one on the wrist and one on the upper arm. Video footage enabled manual counting of the number of pushes (gold standard). Total pushes were averaged across 16 workloads (3 trials of repeated workloads were excluded) for each device and compared to manually counted pushes. Results: Compared to manually counted pushes, SW demonstrated the greatest accuracy (mean difference [MD] compared to video of 2.3 pushes [4.5% error]) and precision (standard deviation of the mean difference [SDMD]) compared to video of 4 pushes, (Coefficient of Variation [CV] =.04), followed by the upper arm-worn accelerometer (MD of 4.4 pushes [10.4% error] and SDMD of 10, [CV= .06]) and the wrist-worn accelerometer (MD of 12.6 pushes [27.8% error] and SDMD of 13 [CV=.15]). Conclusions: SW demonstrated greater accuracy and precision than ActiGraph accelerometers placed on the upper arm and wrist. The accelerometer placed on the upper arm was more accurate and precise than the accelerometer placed on the wrist. Future investigations should be conducted to identify the source(s) of inaccuracy among wearable push counters.